Pelatihan Pembuatan Foto Produk Menggunakan Kamera Handphone dan Peralatan Sederhana untuk Membantu Menaikkan Daya Pemasaran UMKM di Desa Karangtengah, Kecamatan Cepiring, Kabupaten Kendal - Diyar Husni, Muhammad Fahd; Nursanty, Eko; Krismawanti (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
It is considering that the market has now switched to digital through the world of social media. Skills in attracting buyers and digital marketing need to be improved for Home Industry entrepreneurs to compete and survive in the industrial market. By providing training in product photo making, at least it can provide new insights and knowledge that good product photos do not have to be done with sophisticated equipment and in a luxurious studio. However, producing interesting product photos can be done with a simple photo trick, like using only a handphone camera that almost everyone has, minimal software application, and simple equipment that helps to improve the results later. After delivering the theory and direct experiments, it is hoped that the knowledge and skills gained will continue to be remembered, utilized, honed, and continuously developed by themselves. Trial and error using more advanced photo editing application software that is widely available on mobile devices today, both free and paid. In the end, making attractive product photos, of course, will become a good weapon and increase competition in marketing Home Industry products, and the goal is to attract many buyers.